Canadian International Petroleum Conference 2004
DOI: 10.2118/2004-229
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Simulation Analysis of Fractured Reservoir Experiencing Different Stress Conditions

Abstract: Flow through the fracture is usually estimated by cubic law, which assumes flow to occur between two parallel plates. The cubic law is valid to represent the flow through the fracture system if the matrix permeability is very low to provide any significant flow contribution. However, in high permeability rocks, the flow occurs through both fracture and matrix systems. Flow through matrix may sometimes exceed that through the fractures under increased stress acting on the reservoirs. Under these circumstances, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
(5 reference statements)
0
3
0
2
Order By: Relevance
“…The fractures were also represented by unit porosity because it was artificially made with a saw (Guzman, R.E. and Aziz, K. 1992;Muralidharan, V. et al 2004). Fig.…”
Section: Simulation Results History Matching the Experimental Resultsmentioning
confidence: 99%
“…The fractures were also represented by unit porosity because it was artificially made with a saw (Guzman, R.E. and Aziz, K. 1992;Muralidharan, V. et al 2004). Fig.…”
Section: Simulation Results History Matching the Experimental Resultsmentioning
confidence: 99%
“…There is no clear standard method used in analyzing the sensitivity of fractures. According to laboratory investigations, under normal pressure, the stress sensitivity of natural fractures is strong with great potential of aperture variation (Khan et al, 2000;Muralidharan et al, 2004;Petunin et al, 2011). Xiang et al (2003) has studied the stress sensitivity of fracture-pore reservoir system, and believed that the stress sensitivity of artificial fractures, natural fractures and pore types of carbonate rock samples weakened sequentially.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the breakthrough time was reduced significantly and a much higher recovery was obtained with viscosified water followed by CO 2 compared to continuous CO 2 injection. • Muralidharan et al (5) conducted experimental and simulation studies to investigate the effect of different stress conditions (overburden pressure) on fracture/matrix permeability and fracture width. They concluded that during constant injection, average fracture permeability decreased by approximately 91% and the average mean fracture aperture decreased approximately 71%, while increasing overburden pressure from 500 -1,500 psi.…”
Section: Introductionmentioning
confidence: 99%